Titik Temu Mistisisme Islam dan Mistisisme Jawa; Studi Analitis terhadap Persinggungan Ajaran Tasawuf dan Kejawen - Ahmad Yuzki Faridian Nawafi (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
This article discusses the mysticism contained in Islam and Javanese culture. Islamic mysticism is known as Sufism while Javanese mysticism is known as mysticism. Sufism and kebatinan as mystical teachings have the same goal of becoming a perfect human being by the union of a being with a creator. These two teachings then have several similarities, such as in the matter of being united with God as a perfect human endeavor. Then in the process or effort to achieve these goals and the need for a guide in carrying out the mystical process.